Autoimmune myasthenia gravis. - Jayawant, S; Parr, J; Vincent, A (2013)
Myasthenia gravis in children can be generalized or ocular, and associated with antibodies to acetylcholine receptors or muscle-specific kinase, but it can be negative for those antibodies (seronegative). It needs to be distinguished from congenital myasthenic syndromes and other neuromuscular diseases. In the perinatal period, transient neonatal myasthenia and arthrogryposis multiplex congenita, due to maternal antibodies, need to be considered. Juvenile myasthenia is similar in presentation and treatment to that in adults. Here we present guidelines for recognition, diagnosis, and treatment.